Reusing Coal Waste as a Blending Material for Hollow Block Production to Boost Circular Economic of FABA - Syaiful, Syaiful; Putranto, Dinar Dwi Anugerah; Bizzy, Irwin (Program Pascasarjana Universitas Sriwijaya, 2023)
In the world and Indonesia, coal is one of the primary fuel sources for steam power plants (PLTU). This is due to the shrinking and increasing prices of fuel oil. With the abundance of coal energy sources, it continues to be used as the primary energy source for power plants in Indonesia. The economic efficiency obtained can reach 80% compared to the use of solar. However, Fly ash and Bottom ash (FABA), or solid waste produced from the coal combustion process at the PLTU, contains many inorganic minerals, which can pollute the environment, such as air and soil pollution. Conventionally, regarding economic law, Construction and Demolition (C and D) in the circulation system between materials and products must have zero material value and no longer produce residual waste in final disposal. This research implements Circular Economy (CE) to minimize the negative impact of FABA on the environment at PLTU. The experiment used FABA Coal as a mixed material to make Hollow Blocks with six combinations of sizes. The results obtained, the greater the percentage of FABA used, can minimize production costs and improve the quality of hollow blocks. From an economic cost analysis, using FABA for mixed materials for open block production will provide 55% greater economic benefits and 34.67% higher quality Hollow blocks compared to the composition of materials without FABA mixture.